2013
DOI: 10.1186/2041-9139-4-26
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of eye development in the darkness of caves: adaptation, drift, or both?

Abstract: Animals inhabiting the darkness of caves are generally blind and de-pigmented, regardless of the phylum they belong to. Survival in this environment is an enormous challenge, the most obvious being to find food and mates without the help of vision, and the loss of eyes in cave animals is often accompanied by an enhancement of other sensory apparatuses. Here we review the recent literature describing developmental biology and molecular evolution studies in order to discuss the evolutionary mechanisms underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
91
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 122 publications
(92 citation statements)
references
References 91 publications
1
91
0
Order By: Relevance
“…Most insights into sensory reduction concern animal eyes, which usually have thousands of sensory neurons and several peripheral processing centres, and energy expenditure, therefore, maybe especially high, while this argument may be much less obvious when a sensory organ with only two sensory neurons is lost. Current research has indicated that natural selection against eye formation is in effect, however, with a possible role also for genetic drift (Klaus et al 2013;Rétaux and Casane 2013). For hearing organs, direct data on energetic costs are lacking so far, but they almost certainly also differ between types of ears.…”
Section: Selective Forces Shaping the Function Of Tympanal Earsmentioning
confidence: 97%
“…Most insights into sensory reduction concern animal eyes, which usually have thousands of sensory neurons and several peripheral processing centres, and energy expenditure, therefore, maybe especially high, while this argument may be much less obvious when a sensory organ with only two sensory neurons is lost. Current research has indicated that natural selection against eye formation is in effect, however, with a possible role also for genetic drift (Klaus et al 2013;Rétaux and Casane 2013). For hearing organs, direct data on energetic costs are lacking so far, but they almost certainly also differ between types of ears.…”
Section: Selective Forces Shaping the Function Of Tympanal Earsmentioning
confidence: 97%
“…Together with the case of the gustatory/visual trade-off previously described (Yamamoto et al, 2009), these constitute the only examples to date of a direct link between the development of two sensory organs, involving a pleiotropic effect of these signaling systems, and suggesting indirect selection as an evolutionary driving force underlying the loss of eyes in CF (Jeffery, 2010;Retaux and Casane, 2013). In F2 hybrids, however, we did not observe an inverse correlation between lens and OE size, further suggesting that the developmental trade-off has a multigenic determinism.…”
Section: Specific Considerations Of Cf Developmental Evolution and Phmentioning
confidence: 99%
“…; Niven and Laughlin ). A particularly interesting emergent question is whether there is a common morphological mechanism or pattern to this process, or if it is driven randomly by neutral mutation or pleiotropy (Rétaux and Casane ). Eyes are likely to have evolved more than 40 times among animals and take many different forms (von Salvini‐Plawen and Mayr ).…”
mentioning
confidence: 99%